2001
DOI: 10.1029/2000ja000106
|View full text |Cite
|
Sign up to set email alerts
|

North‐south flows observed in the outer heliosphere at solar minimum: Vortex streets or corotating interaction regions?

Abstract: Abstract. During the last two solar minima in the distant heliosphere the equatorial heliospheric plasma velocity oscillated perpendicular to the ecliptic plane with an approximately 26-day period in the distant heliosphere. Two explanations have been proposed: compressive interactions between streams and velocity shear interactions that produce a Kfirmfin vortex street. The latter interpretation has been challenged on the basis that the velocity jumps are supersonic, thereby suppressing the Kelvin-Helmholtz (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“… Burlaga [1990] and Veselovsky [1990] suggested that a vortex street was observed by V2 at ≈25 AU during 1987, and Burlaga and Richardson [2000] provided additional evidence that a vortex street was observed by V2 at 47 AU during 1995, approaching solar minimum. The model of Goldstein et al [2001] that includes both velocity shears and compressive MHD effects predicts a depletion of magnetic flux and density in the distant heliosphere near solar minimum. Thus, it is possible that the departures of the observations from Parker's model in 1987 and 1997 in Figure 2 are associated with the presence of a vortex street at those times.…”
Section: Radial Variation Of the Magnetic Field Strengthmentioning
confidence: 99%
“… Burlaga [1990] and Veselovsky [1990] suggested that a vortex street was observed by V2 at ≈25 AU during 1987, and Burlaga and Richardson [2000] provided additional evidence that a vortex street was observed by V2 at 47 AU during 1995, approaching solar minimum. The model of Goldstein et al [2001] that includes both velocity shears and compressive MHD effects predicts a depletion of magnetic flux and density in the distant heliosphere near solar minimum. Thus, it is possible that the departures of the observations from Parker's model in 1987 and 1997 in Figure 2 are associated with the presence of a vortex street at those times.…”
Section: Radial Variation Of the Magnetic Field Strengthmentioning
confidence: 99%
“…Indirect inference of plasma vorticity has been made in many studies, generally by coupling observations with specific models or simulations (e.g., see Goldstein et al, 2001). Deducing vorticity from a single-point measurement implies that only one scalar component can be estimated.…”
Section: Introductionmentioning
confidence: 99%
“…One could expect such large-scale structures to be observed in the heliosphere. There is an indication of north-south flows in Voyager 2 observations at 47 AU (Burlaga & Richardson 2000;Goldstein et al 2001). The flow pattern showed features of a heliospheric vortex street.…”
Section: Discussionmentioning
confidence: 99%
“…These structures are characterized by large-amplitude modulation of the background plasma parameters, nonoscillatory shape, and usually finite size. There are indications of such coherent structures in a form of vortex streets in solar wind observations (Burlaga & Richardson 2000;Goldstein et al 2001). The Kubo number R ¼ ð B=B 0 Þðl k =l ?…”
Section: Introductionmentioning
confidence: 99%